Field-dependent specific heat of the canonical underdoped cuprate superconductor $$\hbox {YBa}_2\hbox {Cu}_4\hbox {O}_8$$ YBa 2 Cu 4 O 8 - Jeffery L. Tallon (Nature Portfolio, 2020)
Abstract The cuprate superconductor $$\hbox {YBa}_2\hbox {Cu}_4\hbox {O}_8$$ YBa 2 Cu 4 O 8 , in comparison with most other cuprates, has a stable stoichiometry, is largely free of defects and may be regarded as the canonical underdoped cuprate, displaying marked pseudogap behaviour and an associated distinct weakening of superconducting properties. This cuprate ‘pseudogap’ manifests as a partial gap in the electronic density of states at the Fermi level and is observed in most spectroscopic properties. After several decades of intensive study it is widely believed that the pseudogap closes, mean-field like, near a characteristic temperature, $$T^*$$ T ∗ , which rises with decreasing hole concentration, p. Here, we report extensive field-dependent electronic specific heat studies on $$\hbox {YBa}_2\hbox {Cu}_4\hbox {O}_8$$ YBa 2 Cu 4 O 8 up to an unprecedented 400 K and show unequivocally that the pseudogap never closes, remaining open to at least 400 K where $$T^*$$ T ∗ is typically presumed to be about 150 K. We show from the NMR Knight shift and the electronic entropy that the Wilson ratio is numerically consistent with a weakly-interacting Fermion system for the near-nodal states. And, from the field-dependent specific heat, we characterise the impact of fluctuations and impurity scattering on the thermodynamic properties.